APPLYING QUIZIZZ APPLICATION AS AN ASSESSMENT TOOL FOR EFL STUDENTS - Yessicka Noviasmy; Nurul Hasanah; Ambo Dalle (Inspiring: English Education Journal, 2023)
Quizizz is a free online-based formative assessment tool that allows the teacher to conduct both assessments in class or online teaching. This study used Quizizz as an assessment tool for the midterm exam of the first semester English department or EFL students in IAIN Parepare. The method used is technology-based applied research. The instrument used was a midterm exam for the English department students. The midterm exam consists of 15 questions with multiple choice question types. This exam was attended by 18 students. The questionnaire was made using a Mentimeter. The use of Quizizz has a good and positive impact and response. The level of accuracy of students' success in answering questions correctly in this class was 78%. The highest score is 100% and the lowest is 61%. Then 85% prefer Quizizz as an assessment tool compared to paper and google forms.